Phytocenotic characteristics of populations with participation of Crataegus ambigua of gorge Akmysh 2 and Botakan (Western Karatau) (Experimental biology, 2017)
Results of field researches of natural populations of a rare and endangered species of a Crataegus ambigua in natural populations of the Western Karatau are presented in article. The purpose of present research was identification of specific structure of populations of Crataegus ambigua in gorges Akmysh 2 and Botakan with the analysis of age structure of communities.Researches are conducted by route and reconnoitring methods, at field inspections the full specific and taxonomical structure of plants, tiers and age structure of communities is analysed.Results of researches have allowed to define Crataegus ambigua – Rhamnus sintensii – Herba varia community in the gorge Akmysh 2 and Herba varia – Crataegus ambigua community in the gorge Botakan. In both communities the specific structure vary from 34 to 39 species; grassy perennial, annual and biennial  plants prevail. The dominating families are Poaceae, Lamiaceae, Asteraceae, Fabaceae, Brassicaceae. Communities are defined as full.The ratio of age groups of hawthorns shows that population in the gorge Akmysh 2 can be characterized as the young, steady, developing with prevalence the virgin and young generative individuals; hawthorn population in the gorge Botakan can be characterized as middle-aged steady, with domination of young generative plants.The received results allow to estimate stability of populations of Crataegus ambigua in the Western Kazakhstan, to develop actions for his protection in nature.
Keywords: Western Karatau, gorge Akmysh 2, gorge Botakan, Crataegus ambigua, community.